The Development of Quality Improvement Education Program of the National Cancer Grid – EQuIP- India (Enable Quality Improve Patient Care), and Its Impact on the Quality of Cancer Care in India - Vallath, Nandini; Kannan, R. Ravi; Lewis, Shirley; Augustine, Priyanka; Lorenz, Karl; Mickelsen, Jake; Sundararaj, Jenifer Mugesh; Shenoy, Praveen Kumar; Malik, Kapil; Banik, Rinisha; Laskar, Sarbani; Pramesh, C.S. (Indian Journal of Medical and Paediatric Oncology, 2025)
Quality attributes in health care setting include safety, effectiveness, patient centeredness, timeliness, efficiency, and equity. Quality of care outcomes depend not only on the clinical interactions between clinicians and patients but also on the effective alignment and integration of team efforts, logistics, and care processes. The National Cancer Grid (NCG), with its mandate to facilitate and promote quality standards in patient care across India, facilitated quality improvement (QI) training as a key initiative in order to develop competencies within the clinical teams in QI methodology and to strengthen the quality of cancer care processes across cancer centers in the country.The aim of the study was to describe the inception and evolution of the NCG-QI-Hub, its flagship QI training program, EQuIP India (Enabling Quality, Improve Patient Care) to the present model, to illustrate its journey to self-sufficiency and to share the outcomes of the completed projects.Following a pilot in 2017, the NCG-QI-Hub, in partnership with Stanford Medicine, initiated a mentored QI training program using A3 QI methodology and tools to address quality issues impacting cancer care settings. The trainees used the A3 method of thinking and experienced the plan-do-study-act (PDSA) cycle while improving the identified quality problem.Between 2017 and 2024, 89 QI projects across different domains of cancer care (prevention, treatment, and palliation to survivorship) have been completed. The EQuIP India training program has facilitated the creation of 10 institution-based QI training hubs that conduct in-house QI projects, with 45 national mentors and a growing community of over 300 professionals with competencies in using the methodological steps to conduct QI projects. Based on the follow-up survey done in 2022, more than 70% of alumni institutions continued to be associated with quality improvement project programs. The average project progress score (PPS) achieved at graduation of trainee teams of ≥4.0/5 was sustained across the years of conducting the educational program.EQuIP India immersive QI training program has demonstrated that low-cost, structured QI training programs, contextualized to the institutional culture, are feasible and successful in improving the quality of cancer care. The venture has successfully built national-level QI mentorship capacity formation of institutional QI hubs and has thus triggered a QI culture across alumni NCG centers.
Keywords: quality; quality improvement; methodology; medical oncology; cancer care; education